Developing an index based on GIS and statistical analysis for family support of substance abuser in Terengganu - Hafizan, Juahir; Syed Mohd Hafiz, Syed Omar; Mohd Khairul Amri, Kamarudin; Azli Fairuz, Laki; Nasir, Mohamad (2017)
Family support has a strong impact on individuals and there is no exception in substance abuse recovery process. Family support manages to play a positive role in substance abuse problems. The present study deals with the developing model of family support substance abuser with the combination method of Geographic Information System (GIS) and statistical models. The data used for this study was collected from seven districts in Terengganu with a constant number of respondents. 35 respondents for each district were involved in this study. It was then processed using factor analysis (FA) to develop index of family support. By using the developed indices, GIS tool was used to plot the distribution map of family support indices according to each form of family support. The result indicated that the highest index for all form of family support abuser was located in Besut district. High level of family support is essential as an effort for rehabilitation process of substance abusers.